ANNOUNCED REASONS AND ANTICIPATED RESULTS OF SHARE REPURCHASE PROGRAMS – CASE OF WARSAW STOCK EXCHANGE COMPANIES - Wrońska-Bukalska, Elżbieta (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
The article aims to present the meaning of the share repurchase (also called as buy back or buy-back) programmes and to identify the reasons announced and potential results of share repurchase made by firms listed on the Warsaw Stock Exchange (WSE) in Poland. The main hypothesis to be verified states that there are more reasons to repurchase shares than just cash transfer to shareholders and there are different results than just diminishing cash holding. The problem is significant enough because share repurchase in the literature is deemed as a substitute for dividends and as another way for cash transfer to shareholders On carrying out the research for the selected listed companies, I found that shares might be repurchased for many different reasons and not only to signal the excessive amounts of cash held in the corporation. Viewing by the numbers it is possible to state that transferring cash is the least important reason while repurchasing shares.